A 63‐bp insertion in exon 2 of the porcine KIF21A gene is associated with arthrogryposis multiplex congenita. (20th July 2020) - Fang, Z.‐H.; Nosková, A.; Crysnanto, D.; Neuenschwander, S.; Vögeli, P.; Pausch, H.
Summary: A recessive form of arthrogryposis multiplex congenita (AMC) was detected 20 years ago in the Swiss Large White (SLW) pig population. A diagnostic marker test enabled the identification of carrier animals, but the underlying causal mutation remains unknown. To identify the mutation underlying AMC, we collected SNP chip genotyping data for 11 affected piglets and 23 healthy pigs. Association testing using 47 829 SNPs confirmed that AMC maps to SSC5 ( P  = 9.4 × 10 −13 ). Subsequent autozygosity mapping revealed a common 6.06 Mb region (from 66 757 970 to 72 815 151 bp) of extended homozygosity in 11 piglets affected by AMC. Using WGS data, we detected a 63‐bp insertion compatible with the recessive inheritance of AMC in the second exon of KIF21A gene encoding Kinesin Family Member 21A. The 63‐bp insertion is predicted to introduce a premature stop codon in KIF21A gene (p.Val41_Phe42insTer) that truncates 1614 amino acids (~97%) from the protein. We found that this deleterious allele still segregates at a frequency of 0.1% in the SLW pig population. Carrier animals can now be detected unambiguously and excluded from breeding.